Garlic—Allium sativum L. - James M. Stephens (EDIS, 2003)
This document provides an overview of garlic (Allium sativum L.), detailing its botanical characteristics, varieties, and cultivation practices in Florida. It highlights the differences between garlic and onions, describes notable garlic types such as Creole, Italian, elephant garlic, and rocambole, and outlines propagation methods using cloves. The document also includes guidance on planting seasons, climate tolerance, and post-harvest curing and storage techniques to ensure successful growth and preservation. Original publication date May 1994.